Tryptophan Alleviates Acute Heat Stress-Induced Impairment of Antioxidant Status and Mitochondrial Function in Broilers - Ouyang, Jingxin; Zhou, Hua; Li, Qiufen; Zheng, Jun; Chen, Chun; Guo, Shuaipeng; You, Jinming; Li, Guanhong (Frontiers in Veterinary Science, 2022)
Heat stress has been considered as a critical risk factor for decreasing performance and causing oxidative stress in broilers. The tryptophan (TRP) derivative 5-hydroxytryptophan has been reported to protect membrane fluidity in broilers suffering from oxidative stress. Therefore, this experiment was conducted to investigate the effects of dietary TRP supplementation on antioxidant status and mitochondrial function-related genes expressions in broilers exposed to acute heat stress (34 ± 1°C, 24h). Female Arbor Acres broilers (19-d-old, n = 180) were randomly assigned to 1 of 3 treatments. Broilers were fed a basal diet and in the thermoneutral conditions (TN, 23 ± 1 °C) was considered as the TN group. Broilers were fed a basal diet and exposed to acute heat stress (HS, 34 ± 1 °C) was regarded as the HS group. Broilers were fed a basal diet supplemented with 0.18% L-tryptophan and under HS conditions was treated as the HS + TRP group. Heat stress led to increased malondialdehyde (MDA) concentration (P < 0.05), while it elevated catalase (CAT), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and total antioxidant capacity activities (T-AOC) (P < 0.05) compared with the TN group. Nevertheless, compared with the HS group, TRP supplementation increased SOD activity (P < 0.05). The effects of acute heat stress were associated with increased mRNA abundance for redox-related genes (P < 0.05), and reduced mRNA levels for mitochondrial function-related genes (P < 0.05). Notably, the effects of acute heat stress on mitochondrial function-related genes expressions were reversed by TRP treatment. Collectively, dietary 0.18% TRP supplementation beneficially protects against acute heat stress-induced oxidation stress and mitochondrial dysfunction by regulating antioxidant states and increasing mitochondrial function-related genes expressions in broilers.